Perbandingan Metode Pemijahan Terhadap Fertilitas Embrio Ikan Zebra - Khusna, Vinanta Dea Zakiyyatul (Journal of Comprehensive Science, 2025)
Zebrafish (Danio rerio) are vertebrate animals that have been widely developed in the field of research. The increasing use of experimental animals makes zebrafish an alternative to experimental animals. Zebrafish are fish that are easy and fast to breed and meet the principle of replacement. Spawning zebrafish in the wild takes place naturally in nature and can be manipulated in the aquarium. The stages carried out in this study are to compare the number of males and females spawned and the media used during the spawning process. There are 6 groups, namely group 1 male and female ratio 1:1 using spawn trap, group 2 ratio male and female 1:2 using spawn trap, group 3 ratio male and female ratio 2:1 using spawn trap, group 4 ratio male and female ratio 1:1 using marbles, group 5 ratio male and female ratio 1:2 using marbles, and group 6 ratio male and female ratio 2:1 using marbles. The results of this study show that the ratio of male and female zebrafish to 1:2 with the strimin method has the highest fertility of 99.4% and the highest number of embryos, which is with an average of 371.7 eggs with the marble method of male and female ratio of 1:2.